Locution or collocation: comparing linguistic and statistical methods for recognising complex prepositions - Oliveira, Claudia; Nogueira, Cícero; Garrão, Milena (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
Multi–Word Expressions (MWE) include a large range of linguistic phenomena, such as nominal compounds and institutionalized phrases. These expressions, which can be syntactically and/or semantically idiosyncratic in nature, are frequently used in everyday language as well as in formal contexts. In this work we investigate a type of MWE, the complex preposition (CP). The purpose is to establish the relationship between the notions of locution - the linguistic view of CPs - and collocation - the statistical view - when we look into the corpus, and to consider how these notions can be applied to the delimitation of CPs.